2010
DOI: 10.1016/j.brat.2010.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Dialectical behavior therapy skills use as a mediator and outcome of treatment for borderline personality disorder

Abstract: A central component of Dialectical Behavior Therapy (DBT) is the teaching of specific behavioral skills with the aim of helping individuals with Borderline Personality Disorder (BPD) replace maladaptive behaviors with skillful behavior. Although existing evidence indirectly supports this proposed mechanism of action, no study to date has directly tested it. Therefore, we examined the skills use of 108 women with BPD participating in one of three randomized control trials throughout one year of treatment and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
214
3
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(243 citation statements)
references
References 56 publications
14
214
3
12
Order By: Relevance
“…A central component of dialectical behavior therapy (DBT) is to teach specific behavioral techniques with the purpose of helping the individual with borderline personality disorder (BPD) replace maladaptive behavior with functional skills. In one study the researchers [27] found that the participants treated with DBT employed three times as many skills at the end of treatment than before the treatment compared to a control group. The use of skills also indicated a reduction of suicide attempts, depression, and an improved control of aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A central component of dialectical behavior therapy (DBT) is to teach specific behavioral techniques with the purpose of helping the individual with borderline personality disorder (BPD) replace maladaptive behavior with functional skills. In one study the researchers [27] found that the participants treated with DBT employed three times as many skills at the end of treatment than before the treatment compared to a control group. The use of skills also indicated a reduction of suicide attempts, depression, and an improved control of aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Training these behavioral techniques can help in decreasing the stability of disruptive behavior and impulse control disorders. In a study, [20] evaluated the effectiveness of dialectical behavior therapy in emotional regulation. They came to the conclusion that dialectical behavior therapy is a treatment designed particularly for the individuals who show selfinjurious behaviors such as self-injury, suicidal thoughts, desire to commit suicide and suicide attempts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Como uma das estratégias terapêuticas na TCD é ensinar habilidades em áreas em que há déficits (Neacsiu et al, 2010), o terapeuta, deve então, com flexibilidade, estar atento para essa estratégia do paciente e ensinar as habilidades para resolver o problema, e não os resolver por ele.…”
Section: Flexibilidade E Versatilidadeunclassified
“…Essa abordagem foi desenvolvida pela psicóloga Marsha Linehan e é considerada um tipo de terapia cognitivo-comportamental que emprega diversas estratégias baseadas em técnicas de aceitação, métodos e conceitos da ciência comportamental, práticas incorporadas da prática zen e outros métodos contemplativos, tais como mindfulness (McMain, Korman & Dimeff, 2001), com o intuito de viabilizar um tratamento mais efetivo para indivíduos com grave desregulação emocional, como as observadas no diagnóstico de TPB (Blennerhassett & O'raghallaigh, 2005). Desde então, pesquisas vêm sendo realizadas demonstrando sua eficácia (Kröger et al, 2010;Neacsiu, Rizvi & Linehan, 2010). A dialética fundamental nessa abordagem é entre validação e aceitação dos pacientes como eles são, ao mesmo tempo em que se auxilia na mudança do que se tornaram.…”
Section: Introductionunclassified